2014
DOI: 10.1016/j.jcmg.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

3D Echocardiographic Location of Implantable Device Leads and Mechanism of Associated Tricuspid Regurgitation

Abstract: 3D TTE showed a clear association between device lead position and TR. To minimize TR induced by device-leads, 3D TTE guidance should be considered for placement in a commissural position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(122 citation statements)
references
References 35 publications
8
107
1
Order By: Relevance
“…28 However, lead location has not been shown to affect tricuspid regurgitation 29 but use of 3D echocardiography to evaluate the etiology of tricuspid regurgitation may be useful. 29,30 3D echocardiography may also aid in determining torque force of the patients ventricle, 31 unfortunately this sophisticated imaging was not performed. Furthermore, subcutaneous ICD (S-ICD) may eliminate the risk of tricuspid regurgitation associated with endovascular leads.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, lead location has not been shown to affect tricuspid regurgitation 29 but use of 3D echocardiography to evaluate the etiology of tricuspid regurgitation may be useful. 29,30 3D echocardiography may also aid in determining torque force of the patients ventricle, 31 unfortunately this sophisticated imaging was not performed. Furthermore, subcutaneous ICD (S-ICD) may eliminate the risk of tricuspid regurgitation associated with endovascular leads.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with implanted devices, reconstructed images were carefully reviewed to determine the position of the device-lead relative to the TV leaflets. 13 After the 3D TV screening and an in-depth chart review, FTR was categorized into the following 4 types: (1) FTR because of the leftsided heart disease (valve disease or left ventricular dysfunction), (2) FTR because of any cause of pulmonary arterial hypertension (chronic lung disease, pulmonary thromboembolism, left-to-right shunt disease, or Doppler estimated systolic pulmonary artery pressure of >50 mm Hg without an identifiable clinical cause), (3) FTR because of any cause of RV dysfunction (myocardial disease or RV ischemia/ infarction), and (4) FTR with no detectable cause of TR other than chronic AF.…”
Section: D Tv Screening and Ftr Subgroup Determinationmentioning
confidence: 99%
“…We recently reported on an observational study 15 that described the use of three-dimensional (3D) echocardiography for the visualization of device leads as they traverse the TV. We found that TR was present when implanted device leads were interfering with the normal TV leaflet motion.…”
mentioning
confidence: 99%